POLITICAL DEFECTION DAN PERPECAHAN INTERNAL PKB PADA PILKADA PASURUAN 2024 - Fajri Assidiq (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study examines the phenomenon of political defection and internal divisions within the National Awakening Party (PKB) in the process of nominating candidates for the 2024 Pasuruan Regency elections. Using a qualitative approach, this study utilizes in-depth interviews with party officials at the branch and regional levels, analysis of organizational documents, and media coverage to understand the dynamics of the conflict. Data analysis is conducted inductively through a process of reduction, presentation, and conclusion drawing, accompanied by thematic analysis to identify patterns of causes of division, the dynamics of candidate nomination, and their impact on electoral strategies. Source and technique triangulation is applied to enhance the validity of the findings. The results of the study show that internal divisions were triggered by competing interests among elites in determining candidates for regional leadership positions. The candidate selection mechanism, which was considered to not fully reflect the aspirations of grassroots cadres, further exacerbated tensions and led to dissatisfaction among party structures. In addition, political intervention from external coalitions and actors outside the PKB has put additional pressure on the party, exacerbating internal differences. This situation has had a direct impact on the weakening of organizational consolidation, disrupting the solidarity of the party machine and dividing the PKB's voter base in a number of strategic areas. This study emphasizes the importance of strengthening party institutions through increased transparency and accountability in the candidate selection process, as well as the need for more effective internal conflict resolution mechanisms. These efforts are considered crucial to prevent political defections and maintain organizational cohesion in the next electoral contest.